2021
DOI: 10.1155/2021/6635198
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Propagative Waves in a Periodically Supported Rail Using Periodic Structure Theory

Abstract: This paper presents the numerical study on propagative waves in a periodically supported rail below 6000 Hz. A periodic rail model, which considers the effects of both the periodic supports and the rail cross section deformation, has been established based on the periodic structure theory and the finite element method. Two selection approaches are proposed to obtain the concerned dispersion curves from the original calculation results of dispersion relations. The differences between the dispersion curves of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It can be confirmed that the distance attenuation tends to be high, near 160 and 1000 Hz, where the eigen modes exist. Theoretically, it is known that the wave does not propagate at the frequencies of the eigen mode [38]. It is considered that this effect occurred as an increase in apparent distance attenuation.…”
Section: Spatial Distribution Of Group Velocity and Distance Attenuationmentioning
confidence: 99%
“…It can be confirmed that the distance attenuation tends to be high, near 160 and 1000 Hz, where the eigen modes exist. Theoretically, it is known that the wave does not propagate at the frequencies of the eigen mode [38]. It is considered that this effect occurred as an increase in apparent distance attenuation.…”
Section: Spatial Distribution Of Group Velocity and Distance Attenuationmentioning
confidence: 99%